Penanaman Karakter Positif Calon Guru Bahasa Indonesia Berbasis Studi Kasus Pelanggaran Etika Komunikasi - Pangastuti, Miftah Widyan (Jurnal Lentera merupakan Jurnal Prodi Pendidikan Bahasa Indonesia yang berkala mempublikasikan artikel ilmiah dari hasil penelitian berupa pengajaran dan pendidikan Bahasa Indonesia. Secara khusus, jurnal ini berisi penelitian tentang pengajaran, pen, 2019)
Positive character building in this research was conducted by changing negative perspective of communication ethics violations case study to appealing sentences. The data collected in the form of screenshots images of the conversations between contact person and customers indicated violations of ethics in communication. The research was a qualitative research with descriptive analysis technique. It described social events based on the real facts. The research resulted in positive character building based on communication ethics violation findings consisting of contact person’s privacy violation and excessive request or hopes to contact person.